Kesehatan Mental Mahasiswa dalam Perspektif Islam: Menyikapi Tugas, Tuntutan, dan Tekanan Sosial Dengan Keteguhan Iman - Oktarosada, Dwi; Nurul Fadilah; Oriza Sativa (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This study examines the mental health of university students from an Islamic perspective, focusing on how students cope with academic tasks, demands, and social pressures through the strength of faith. The main issue addressed is the high level of stress and mental disorders among students caused by academic burdens, social expectations, and a lack of understanding and support regarding mental health. The study aims to identify factors influencing students' mental health and analyze the role of Islamic values as a spiritual solution to these pressures. A descriptive quantitative method was employed, collecting data via online questionnaires distributed to students at Universitas Borneo Tarakan, supported by a literature review. The analysis revealed that academic pressure, social expectations, and limited openness are primary triggers of mental health problems. However, students who practice Islamic principles such as worship, remembrance of God (dhikr), and patience, and who strengthen their spiritual relationship with Allah SWT, tend to have greater mental resilience. The study concludes that an Islamic spiritual approach plays a significant role in helping students manage stress and pressure, thereby enhancing their mental well-being.